Variability in STEM Summer Bridge Programs: Associations with Belonging and STEM Self-Efficacy - Barth, Joan M.; Dunlap, Sarah T.; Bolland, Anneliese C.; McCallum, Debra Moehle; Acoff, Viola L. (Frontiers in Education, 2021)
To address the challenges facing racial minority students majoring in STEM during the transition from high school to college, NSF funded Louis Stokes Alliances for Minority Participation (LSAMP) programs throughout the country implement summer bridge programs. Bridge programs vary in their focus on professional development, academic support, research experiences, social activities, and in other areas, but all share an intention to support students during their transition to college. Beyond retention, little is known about how these varied summer bridge experiences impact student outcomes in the first year of college. This study first describes the variability in the summer bridge programs in the Alabama LSAMP Alliance and then examines how differences in students’ satisfaction with their experiences are associated with feelings of belonging and STEM self-efficacy, two factors associated with STEM retention. Students (N = 145) who attended an LSAMP summer bridge program were surveyed at three time points over the first year of college. Findings indicated that bridge programs varied in their offering of academic classes, academic support (e.g., study skills), research experiences, professional development, and planned social activities. Students attending HBCUs scored more favorably than students at PWIs on some measures; however, these differences could be accounted for by satisfaction with bridge experiences. Satisfaction with specific aspects of the bridge programs, especially orientation activities and getting to know other students, were associated with feelings of belonging and STEM self-efficacy. These relations were stronger for belonging. Over the course of the academic year, the relations between bridge satisfaction and belonging and self-efficacy weakened.